Greeting robot - Tan, Wei Shen. (2012)
This report outlines the final year project which was aimed at designing and developing an autonomous greeting robot. An autonomous robot was built using an iRobot base and customized body with several features added to it. The task of this autonomous robot was to perform specific functions such as facial recognition of users within the vicinity and respond with robotic arm gestures and audio outputs.